2011
DOI: 10.1007/s00198-011-1801-0
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of brief high-impact exercises for enhancing bone health in premenopausal women

Abstract: Based on the meta-analysis, brief high-impact exercise improves BMD at the hip but not at the lumbar spine. Effectiveness of this form of exercise as a lifestyle physical activity for prevention of osteoporosis should be explored in larger populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 39 publications
5
40
0
6
Order By: Relevance
“…The protocol regarding the recruitment, instruments and physical exercise intervention for this study follows earlier published and validated designs (20)(21)(22)(23). Briefly, ethical approval for the study was obtained from the local research ethics committee (09/H1204/76) and the institutional ethics review board, and all participants gave written informed consent prior to participation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol regarding the recruitment, instruments and physical exercise intervention for this study follows earlier published and validated designs (20)(21)(22)(23). Briefly, ethical approval for the study was obtained from the local research ethics committee (09/H1204/76) and the institutional ethics review board, and all participants gave written informed consent prior to participation.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the evidence for the osteogenic effectiveness of short, discrete bouts of restinterspersed, high-impact exercise for mature bone (23), this trial was designed to load the bone of premenopausal women with a few loading cycles of mechanical strain for optimum osteogenic response. In the exercise intervention group, participants performed two-legged maximum vertical jumps 10 times using an arm swing in countermovement jump style, barefooted on a relatively hard floor, three days per week for a period of 6 months.…”
Section: Exercise Interventionmentioning
confidence: 99%
“…These results suggest that low-repetition and high-impact jumping may enhance the BMD at the clinically relevant skeletal sites in young women. However, a meta-analysis study demonstrated that brief (<30 min per day, 4.6 days per week) high-impact exercise improves the BMD at the femoral neck, but not at the lumbar spine in premenopausal women [11].…”
Section: Case Reportmentioning
confidence: 97%
“…Furthermore greater muscle forces applying strains on the spine might be expected to reduce vertebral fracture risk by increasing BMD, which also showed a modest genetic correlation with spinal curvature (-0.23) (see Figure 1). That said, a previous meta-analysis suggested the lumbar spine may be relatively unresponsive to mechanical inputs, based on the lack of change in BMD in response to high impact interventions in premenopausal women as compared with the hip (19) . However, the latter finding may simply reflect differences in the contribution of high impact exercise to the local strain environment according to skeletal site, rather than any inherent differences in mechano-responsiveness; in contrast to the hip, intrinsic forces exerted on the spine by paraspinal muscles may be relatively high as compared with extrinsic forces generated through exercise.…”
Section: Thoracic Spinal Curvature: Heritability and Genetic Correlatmentioning
confidence: 99%